PROBLEMATIKA PENASIHAT HUKUM BELUM BERSTATUS ADVOKAT KETIKA MENERIMA SURAT KUASA KHUSUS UNTUK BERACARA DI PENGADILAN (STUDI KASUS PUTUSAN NOMOR 412/PDT.G/2019/PN MDN DI PENGADILAN NEGERI MEDAN) - Bayu Imantoro (President University, 2019)
In representing the parties for proceedings in court or other institutions outside the court, advocates must show the legitimacy of their profession as an advocate. The validity is proven by the existence of a power of attorney from one plaintiff or defendant to an advocate with the designation of an extraordinary power of attorney. Following Article 1795 of the Civil Code: The granting of power of attorney can be carried out precisely, namely only regarding a particular interest or more, or in general, covering all the interests of the person giving the power of attorney. The unique power of attorney is the basis for granting power of attorney to the advocate to take any action that the recipient of the power of attorney may take to represent the interests of the power of attorney as the principal party. The following legal basis, in Article 4 paragraph (1) of Law no. 18 of 2003 concerning Advocates, before carrying out their profession, Advocates must swear an oath according to their religion or make a solemn promise in an open session of the High Court in their legal domicile. When filing a lawsuit, each extraordinary power of attorney is registered at the clerk's office at the judiciary, where it will be listed for data collection and supervision of the attorney. The research aims to analyze the application of Article 4 paragraph (1) concerning advocates who have not yet received an oath when they receive an extraordinary power of attorney from the plaintiff, then register civil cases at the clerk's office and continue to represent the plaintiff, follow the trial process until the judge makes a final decision. The research method used is a normative juridical approach.